Pemeriksaan Aset Tetap Pada PT Bintang Widya Lestari Di Samarinda (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2019)
The purpose of this study was to find out the fairness of the presentation of the value of fixed assets in the financial statements of PT Bintang Widya Lestari at the period that ended December 31st, 2017 and also to find out whether in that application already accordance with Financial Accounting Standards (SAK ETAP) Chapter 15 on Fixed Assets. Analytic tool used in this research is the Financial Accounting Standards (SAK ETAP) Chapter 15 about Fixed Assets and the use of examination worksheet, consisting of: Fixed Assets Top Schedule, Fixed Assets Schedule Supporting, Adjustment Journal, and Working Trial Balance. From the research found that the presentation of the value of fixed assets in the financial statements of PT Bintang Widya Lestari at the period which ended at December 31st, 2017 had not been presented fairly and not yet in accordance with generally accepted accounting principles (GAAP ETAP Chapter 15). This is because there is a difference between the calculation and recording of fixed assets at PT Bintang Widya Lestari with the calculation and recording of fixed assets according to the audit which guided by SAK ETAP Chapter 15 on Fixed Assets.